Pengaruh Kompetensi Guru Terhadap Kinerja Guru Pada SD Se-Nagari Lubuk Basung Kabupaten Agam - Maryuni, Yollanda Putri; Yadewani, Dorris Yadewani; Mulyani, Sri Mulyani (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2024)
Teachers are a component that influences the creation of quality educational processes and outcomes. The aim of this research is to determine the influence of teacher competency on teacher performance in elementary schools throughout Nagari Lubuk Basung, Agam Regency. This type of research is quantitative research. The population in this study was 104 PNS/PPPK teachers at elementary schools in Nagari Lubuk Basung, Agam Regency. The sample size used the Slovin formula, so a sample of 51 respondents was obtained and the sampling technique used random sampling. The data collection technique uses a questionnaire, while the data analysis method uses validity and reliability tests, descriptive statistics, classical assumptions, multiple linear regression analysis, and statistical tests. The results of the research show that partially pedagogical competence, personality competence and professional competence simultaneously have a significant effect on teacher performance, while social competence has no effect and is not significant on teacher performance and simultaneously pedagogical competence, personality competence, social competence and professional competence simultaneously have an effect significant to teacher performance, this shows the influence of all variables on teacher performance. Schools need to improve through collaboration with various parties, namely the government, community, private sector, especially with the education and culture department because quality teachers are the guarantor of the quality of education.